2022
DOI: 10.3390/ijms232214371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Genes for Real-Time Quantitative PCR Analysis in Tissues from Bumble Bees (Bombus Terrestris) of Different Lines

Abstract: Bumble bees are important alternative pollinators and model insects due to their highly developed sociality and colony management. In order to better understand their molecular mechanisms, studies focusing on the genetic and molecular aspects of their development and behavior are needed. Although quantitative real-time polymerase chain reaction (qRT-PCR) can be used to quantify the relative expression of target genes, internal reference genes (which are stably expressed across different lines and tissues) must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, EF1, S18 and S28 were identified as the most stable reference genes based on the outcomes of the other four algorithms (Tables 1 and 2). Moreover, a study on a related insect did not find such striking differences between lab-raised and wild-collected insect tissues [22]. In contrast to these geNorm methods (Tables 1 and 2), seasonal changes significantly alter the gene expression levels in bumblebees, increasing the diversity in reference gene expression.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, EF1, S18 and S28 were identified as the most stable reference genes based on the outcomes of the other four algorithms (Tables 1 and 2). Moreover, a study on a related insect did not find such striking differences between lab-raised and wild-collected insect tissues [22]. In contrast to these geNorm methods (Tables 1 and 2), seasonal changes significantly alter the gene expression levels in bumblebees, increasing the diversity in reference gene expression.…”
Section: Discussionmentioning
confidence: 87%
“…All primers were designed using Primer-BLAST software (NCBI) in accordance with MIQE requirements. Primers from a previous study [22] were used for seven reference genes, and three primers for were newly designed (Table S1). After qRT-PCR validation of the generated primer pairs, the most suitable gene was selected for subsequent experiments.…”
Section: Genes and Primer Designmentioning
confidence: 99%
“…Generally, housekeeping genes encode proteins that are necessary to maintain fundamental biological processes, such as actin (ACT), ubiquitin (UBI), elongation factor (EF), protein phosphatase 2a (PP2a), and tubulin (TUB), which are commonly utilized as internal reference genes [19]. However, increasing experimental evidence has shown that housekeeping genes are not as stable as previously believed in different conditions [20,21]. Several studies have reported that some novel characterized genes exhibit more excellent stability than transitional housekeeping genes under certain conditions.…”
Section: Introductionmentioning
confidence: 99%